Impact of ten influencing factors in the application of new technologies in production by science and technology enterprises - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This article pointed out relevant impacts of ten factors influencing the application of new technologies in production which were respectively classified into three environmental, organizational and technological groups. Clear understanding of the impact as well as difficulties, barriers caused by the factors could help managers of science and technology enterprises making better decision towards effective application of new technologies. Code: 14061801